Transnational return migration of 1.5 generation Korean New Zealanders : a quest for home - Lee, Jane Yeonjae (Korean communities across the world., 2018)
Why do immigrants return home? Is return migration a failure or a success? How do returnees settle back into their original homeland while retaining their connections to their host society? How do returnees contribute to their homeland with their skills gained from overseas? Transnational Return Migration of 1.5 Generation Korean New Zealanders: A Quest for Home seeks to answer these complex questions surrounding return migration through a case study of the 1.5 generation Korean New Zealander returnees. Jane Lee questions and unpacks the very meaning of "home" and "return" through the personal and intimate stories that are shared by the Korean New Zealander returnees. This book tells a compelling story of the strong desire contemporary transnational migrants feel to belong to one particular identity group. In addition, the author highlights the realities and disconnections of transnationalism as the returnees' transnational activities and experiences change over time and space.